The effects of serotonin inhibitors on bone metabolism: literature review - Franco, Rocco; Matteo, Asaro; Gianfreda, Francesco; Miranda, Michele; Bollero, Patrizio; Barlattani, Alberta (Journal of Stomatology, 2020)
Depression is a mood and behavior disorder. It is a very frequent pathology in the world that requires pharmacological treatment using drugs that inhibit the recovery of serotonin. In fact, serotonin is a hormone that creates a feeling of well-being at the level of central nervous system. Serotonin is mainly produced by nerve cells. Therefore, selective serotonin reuptake inhibitors (SSRIs) are mainly used for the treatment of states of anxiety and major depressive disorder. SSRIs increase serotonin level, blocking its resorption in the presynaptic cell. Consequently, an increase in the bioavailability of serotonin in the synaptic junction occur. In fact, at the bone level, according to some observations, it causes an increase in bone resorption. Our study with a systematic review of the literature was to evaluate whether the intake of SSRIs could in any way influence implant survival. “SSRI” and “dental implant” were used as key words in the principal resources. Five articles that met the inclusion criteria were considered. The study found that these drugs can affect the implant survival rate. The data of these articles concerning implant survival have extrapolated. There is an association between intake and implant survival, probably due to a possible link between bone metabolism and drug. Further studies are recommended to effectively evaluate the influence of the drug on implant survival.